The Effect of Using Drama Technique towards the Students’ Speaking Accuracy, Fluency, and Comprehensibility - Julia Marfuah; Andi Patmasari (ELS Journal on Interdisciplinary Studies in Humanities, 2020)
This research intended to prove whether the use of drama technique affected the students’ speaking accuracy, fluency, and comprehensibility or not. This research employed quasi-experimental research design with the non-equivalent control group design. The population of this research was the second year students of senior high school that consisted of 260 students. This research used cluster random sampling technique. From nine classes, two classes were taken as a sample of the research. One class was chosen as the experimental class and another one as the control class. The total sample consisted of 72 students. In order to answer the research question, the instrument of this research was speaking test. The result of data analysis showed that there was no significant different of the students’ speaking accuracy, fluency, and comprehensibility of both classes in pre-test. But the students’ speaking accuracy, fluency, and comprehensibility of both classes in post-test was significant, which means that drama technique can significantly affect the students’ speaking accuracy, fluency, and comprehensibility.